1996
DOI: 10.1203/00006450-199604000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Immunosuppression Is Linked to Rapidly Fatal Disease in Infant Rhesus Macaques Infected with Simian Immunodeficiency Virus

Abstract: Six newborn rhesus macaques were experimentally infected with pathogenic Simian immunodeficiency virus of macaques (SIVmac251), and three newborn macaques were infected with avirulent SIVmac1A11. The former developed rapidly fatal simian AIDS and died within 26 wk of age, whereas the latter remained clinically normal. Infant monkeys that developed rapidly progressive disease had rapid declines in CD4+ cells and were unable to mount IgG and IgA antibody responses to SIV or to an unrelated antigen, tetanus toxoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…The efficacy of the MVA-SIVgpe vaccine is due to the expression of SIV proteins and not simply to infection with MVA vector, since immunization of newborn macaques with MVA expressing measles antigens did not affect viremia or disease course after SIVmac251 challenge (unpublished observations). We previously reported that two of five macaques infected with SIVmac1A11 in utero or at birth were protected from oral SIVmac251 challenge (33). That study differed from the present one, however, in that monkeys were challenged 1 year after SIVmac1A11 infection, which allowed more time for immune responses to mature.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The efficacy of the MVA-SIVgpe vaccine is due to the expression of SIV proteins and not simply to infection with MVA vector, since immunization of newborn macaques with MVA expressing measles antigens did not affect viremia or disease course after SIVmac251 challenge (unpublished observations). We previously reported that two of five macaques infected with SIVmac1A11 in utero or at birth were protected from oral SIVmac251 challenge (33). That study differed from the present one, however, in that monkeys were challenged 1 year after SIVmac1A11 infection, which allowed more time for immune responses to mature.…”
Section: Discussioncontrasting
confidence: 56%
“…The enzyme-linked immunosorbent assays (ELISAs) to detect SIV-specific immunoglobulin G (IgG), cholera toxin-specific IgG, and tetanus toxoid-specific IgG have been described previously (33,47,49).…”
Section: Methodsmentioning
confidence: 99%
“…Initial virus exposure leads to a recognizable, acute viraemia that resolves into a persistent infection phase typified by progressively declining CD4 + T cells, increasing immunodeficiency, wasting disease and death. A consistent finding in several SIV infection studies was the existence of ' nonresponding, rapid progressing ' animals after intravenous inoculation (Letvin & King, 1990 ;Otsyula et al, 1996 ;Zhang et al, 1988). These animals are persistently infected with SIV, make a low or undetectable serum antibody response to virus (nonresponding), and succumb rapidly to AIDS sequelae (Daniel et al, 1985 ;Fultz et al, 1990 ;Kannagi et al, 1986).…”
Section: Introductionsupporting
confidence: 54%
“…This high viremia during the initial weeks of infection resulted in a rapid and early dissemination of virus to all lymphoid tissues. The inability of the untreated animals to mount strong or persistent anti-SIV IgG responses also indicates virus-induced immunosuppression during these initial weeks of infection (32). This inability to control virus replication resulted in rapidly progressive fatal immunodeficiency within 2 to 3 months.…”
Section: Discussionmentioning
confidence: 99%